Conceptual location of parcel lockers in selected towns of the West Pomeranian Voivodship in Poland: A survey study - Ludmila FILINA-DAWIDOWICZ; Joanna SEK; Peter SZILASSY; Oliwia BARTUSIAK (Communications of International Proceedings, 2024)
The development of e-commerce has been observed over the years that impacts the ways of goods distribution. Parcel lockers gain in popularity while delivering goods to the final customers in Poland. Although the parcel lockers network has developed dynamically, there are still challenges associated with the need to extend it, especially in towns and villages. Therefore, the aim of the article is to investigate the opinions of West Pomeranian Voivodship (Poland) residents on the need to develop parcel lockers network and propose a concept of locating new parcel lockers in selected towns of this Voivodship. A questionnaire was developed, and the survey was carried out among the residents of the West Pomeranian Voivodship on the use of parcel lockers. On the basis of obtained opinions analysis, the preferable places of parcel lockers location were determined and the conceptual location of parcel lockers in selected towns in the West Pomeranian Voivodship was proposed. It was concluded that there are prospects for further development of the parcel lockers network in the coming years in the West Pomeranian Voivodship in Poland.
Keywords: parcel locker; transport infrastructure; e-commerce; last mile logistics; distribution